(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Ksenia V. Arzhantseva, Vera B. Shamina (Kazan’, Russian Federation) This article deals with the analysis of narrative structure of British dramatist Harold Pinter’s novel ‘The dwarfs’ in the context of intellectual drama tradition reconstruction. Through the analysis of the main characters of the novel the author has made an attempt to trace the key peculiarities of Pinter’s style. In Russian criticism there are very few works on the novel, mainly due to the fact that it was translated only 16 years after its publication. The processes, typical of new drama and literature on the turn of XXth and XXIst centuries, are also in the focus of this paper. ‘The dwarfs’ written in the early 1950s yet contains the characteristics of the playwright’s style, which have become his hallmarks. The principles, distinguished as attributive of intellectual drama, include dialogization as principal narrative form; thematization of theatre and art as method to objectify the aesthetic and philosophical conception of the author; remarks and intertextuality as form of interaction with the text, where the role of the author is applied to narrator-director. Key words: dwarfs, dialogization, intertextuality, intellectual drama, new drama, mask, play. DOI 10.23683/1995-0640-2019-1-177-185